The choice of transport technology in the presence of exports and FDI - Pontes, José Pedro (2011)
In a set-up with intermediate production, we analyze how a shipper's choice of transport technology, traditional versus modern, interacts with the mode of foreign expansion by an service firm, export versus foreign direct investment (FDI). In terms of the mode of foreign expansion by the service firm, we obtain that: due to trade in intermediate goods, trade and FDI can be complements; the export strategy dominates when the economies of scale at plant level are high and trade costs are low; the FDI strategy is preferable when market size is large and trade costs are intermediate. In what concerns the choice of transport technology by the shipper, we find that: the modern technology tends to be implemented in larger markets; economic integration can encourage the adoption of modern technology vis-à-vis the traditional one; the modern technology adoption is more likely for intermediate levels of transport costs. We then have that modern technology adoption usually occurs under the FDI strategy, since both emerge when trade costs are intermediate and market size is large.